2015
DOI: 10.1007/s10544-014-9904-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bias voltage and temperature on lifetime of wireless neural interfaces with Al2O3 and parylene bilayer encapsulation

Abstract: The lifetime of neural interfaces is a critical challenge for chronic implantations, as therapeutic devices (e.g., neural prosthetics) will require decades of lifetime. We evaluated the lifetime of wireless Utah electrode array (UEA) based neural interfaces with a bilayer encapsulation scheme utilizing a combination of alumina deposited by Atomic Layer Deposition (ALD) and parylene C. Wireless integrated neural interfaces (INIs), equipped with recording version 9 (INI-R9) ASIC chips, were used to monitor the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
89
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(91 citation statements)
references
References 48 publications
2
89
0
Order By: Relevance
“…Typical values for these size silica nanoparticles give uptake values of around 15,000 particles per cell for the RAW 264.7 cell line. 39 Using this uptake value, the calculated radical production (Figure 6), and the typical cellular volume (~ 2 pL), the intracellular concentration of [HO • ] the bare mesoporous and nonporous materials can be calculated to be approximately 800 and 16000 pM, respectively (see SI for full calculation). Since the concentration of hydrogen peroxide used in the EPR experiments is much higher than a true in vivo concentration, this can be used to correct the above concentrations to give realistically expected values (assuming no reaction with other molecules).…”
Section: Resultsmentioning
confidence: 99%
“…Typical values for these size silica nanoparticles give uptake values of around 15,000 particles per cell for the RAW 264.7 cell line. 39 Using this uptake value, the calculated radical production (Figure 6), and the typical cellular volume (~ 2 pL), the intracellular concentration of [HO • ] the bare mesoporous and nonporous materials can be calculated to be approximately 800 and 16000 pM, respectively (see SI for full calculation). Since the concentration of hydrogen peroxide used in the EPR experiments is much higher than a true in vivo concentration, this can be used to correct the above concentrations to give realistically expected values (assuming no reaction with other molecules).…”
Section: Resultsmentioning
confidence: 99%
“…Foutz et al 12 showed that freezing at −70 °C did not affect the in-plane Young’s modulus, loading response and the ultimate tensile strength of rat skin, but significantly lowered its fracture strength12. More recently, in a non-mechanical characterization of skin, Mansoor et al 19 showed that freezing increased the diffusivity of drugs in porcine skin, most likely due to ice crystal formation during the freezing process, which subsequently led to structural damage, increased porosity, and potentiality to changes in the mechanical properties of the skin. The diffusion coefficient of doxorubicin was higher in frozen and thawed porcine skin compared to freshly excised porcine skin.…”
mentioning
confidence: 99%
“…Disposable chips were laser etched (3rd Gen 40W laser, Full Spectrum Laser) into 1/16 inch black acrylic sheets (24112-07, Inventables), cleaned with distilled water, soaked in 70% ethanol for 5 min, dried with compressed air, and enclosed on one side using clear optical film (MicroAmp, Applied Biosystems). Primers were dispensed using a pipette, dried at 70 °C for 10 min, enclosed on the top-side using MicroAmp tape, and chips were stored as previously described (Stedtfeld et al, 2015). The chip configuration consisted of eight reaction wells per sample lane, and four sample lanes per chip (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…Data analysis was performed as previously described (Stedtfeld et al, 2015) to calculate the threshold time (T t ) of LAMP, akin to threshold cycle (C t ). The signal to noise ratio (SNR) was calculated as the signal at a given time minus the median signal at the start of the reaction, divided by the standard deviation of the signal at the start of the reaction.…”
Section: Methodsmentioning
confidence: 99%